Perancangan User Experience Learning Management System (LMS) Menggunakan Metode Goal-Directed Design (Studi Kasus: Rakryan Digital Academy) - Putri Maulidah Hasanah; Lutfi Fanani; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Rakryan Digitalent Hub has a digital competency strengthening program for Vocational High School (SMK) students who are competent in information technology expertise. This program is called Rakryan Digital Academy. This program is carried out in the form of blended learning, namely online and offline learning. To facilitate Rakryan Digital Academy program, Rakryan Digitalent Hub wants a Learning Management System (LMS) platform as a learning media that can be used easily by students. Previously, students used a global platform that did not yet meet stakeholder needs and some of the features that were uncomfortable for students. This research was conducted with the aim of designing a Learning Management System (LMS) using the Goal-Directed Design (GDD) method. In the GDD method, there are 6 steps that must be done. The first stage is the research stage which aims to determine the scope, interviews with stakeholders and potential users, and identifies organizational goals. The next stage is the modeling stage, modeling the characteristics and interactions of potential users in the form of personas and user journey maps. The modeling stage is followed by the requirements stage, which analyzes the needs of potential users and builds the context of the scenario as well as the design of the information structure using card sorting and hierarchical task analysis (HTA). After the needs are collected, the framework stage will be carried out with the aim of building a design framework based on design guidelines. The results of the framework stage will be refined with a refinement stage which results in a high fidelity prototype. After building a solution design, a support stage is carried out to test the level of usability in the learning management system design. The test was carried out using the USE questionnaire by 20 respondents and resulted in a final value of 84.75%. This value is an average of 4 parameters, namely, usefulness, ease of use, ease of learn, and satisfaction which are included in the very good category.